AB0852 Sprifermin Alters Cartilage Morphology and Subchondral Bone Marrow Lesions in Knee Osteoarthritis. (9th June 2015) - Roemer, F.W.; Aydemir, A.; Lohmander, S.; Crema, M.D.; Marra, M.D.; Muurahainen, N.; Felson, D.T.; Guermazi, A.
Abstract : Background: A randomized, double-blind, placebo-controlled phase 1b clinical trial of Sprifermin (rhFGF18) in knee OA assessed central medial tibio-femoral compartment cartilage thickness on quantitative MRI (qMRI) as the structural primary endpoint and reported no statistically significant response 1 . However, the drug was associated with, dose-dependent effects in the lateral tibio-femoral compartment. In the trial, Sprifermin was administered in 2 cycles of 3 weekly intra-articular injections at 10 μg, 30 μg, and 100 μg. In addition to qMRI, MRIs were assessed semi-quantitatively (sq) by expert radiologists. Objectives: To perform post-hoc analyses to assess effects of Sprifermin on sqMRI parameters. Methods: This exploratory analysis focused on changes in the 100 μg subgroup (n=57) and its matching placebo subgroup (n=18) evaluating changes from baseline (BL) up to 12 months. Assessed were cartilage morphology, bone marrow lesions (BMLs), meniscal damage, meniscal extrusion, Hoffa-synovitis and effusion-synovitis using the WORMS scoring system. Analyses included multi-dimensional assessment: a Delta subregional [DSR] approach (including number of subregions [SRs] showing worsening (>0), no change (0) and improvement (<0), i.e. negative values indicating improvement and positive values indicating worsening) - and a Delta-sum [DSM] approach (including total sum of grades for SRs showing worsening, no change, and improvement). Analyses were performed on a whole knee level and separately for medial and lateral tibio-femoral joints (MTFJ, LTFJ), and patello-femoral joint (PFJ). Mann-Whitney-Wilcoxon tests assessed differences between treatment groups. Results: At BL, no significant differences were observed between placebo and treatment groups for all sqMRI parameters, except for whole knee cartilage morphology (29.97±16.00 [standard deviation] for treatment vs. 21.11±14.76 vs. placebo, p=0.04). For change in cartilage morphology, statistically significant differences were seen from BL to 12 months using the DSR approach, with lower values on sprifermin (corresponding to less worsening) vs. placebo for the PFJ (0.22±0.55 vs. treatment 0.02±0.23, p=0.046), with similar results observed using the DSM approach. Also, although not statistically significant, somewhat less worsening vs. placebo was observed in the LTFJ (DSR, 0.11±0.32 vs. treatment 0.05±0.48). For change in BMLs, statistically significant changes from 6 to 12 months were observed for the whole knee, with negative values indicating improvement and positive values worsening (placebo 0.44±1.20 vs. treatment −0.14±1.24, p=0.042), and borderline for LTFJ (0.22±0.65 vs. -0.05±0.80 p=0.064) using the DSR approach. No notable changes from BL were observed for the remaining analyzed parameters. Conclusions: Cartilage morphology showed less worsening from BL to 12 months and BMLs showed improvement after 100 ug Sprifermin treatment from 6 to 12 months. The potential effect of Sprifermin on subchondral bone (BMLs) is a novel finding that warrants further exploration. This finding may be explained by altered loading as a result of cartilage surface restoration or by direct effects on bone. References: Lohmander et al., Arthritis Rheumatol 2014;66:1820-31. Disclosure of Interest: F. Roemer Shareholder of: Boston Imaging Core Lab, LLC., A. Aydemir Employee of: EMD Serono, S. Lohmander: None declared, M. Crema Shareholder of: Boston Imaging Core Lab, LLC., M. Marra Shareholder of: Boston Imaging Core Lab, LLC., N. Muurahainen Employee of: EMD Serono, D. Felson: None declared, A. Guermazi Shareholder of: Boston Imaging Core Lab, LLC., Consultant for: TissueGene, OrthoTrophix, Merck Serono, and Genzyme